"The Me I Want You to See": The Use of Video Game Avatars to Explore Identity in Gifted Adolescents. Issue 2 (April 2020) - Wood, Susannah M.; Szymanski, Antonia
Gifted adolescents may identify as "gamers" who create avatars to navigate video games and cell phone apps. Avatars provide a unique venue through which gifted teens can explore the issues of self and identity in a critical time of their development. The purpose of this article is to (a) provide an overview of what avatars are, (b) explain how avatars can be a venue to explore concepts of identity for gifted students, and (c) suggest how educators can utilize the concept of avatars in their classroom activities. We provide questions that educators can use to facilitate dialogue with their gifted adolescents about avatars and identity.